Ta'tsiir Istikhdaam Namuudzaj La'b al-Adwaar 'Ala Mahaarat al-Kalam Ladaa al-Thalabat Fii al-Madrasat al-Hukuumiyyat 1 Padang - Erlanda, Titi; Hanomi, Hanomi; Rahmawati, Rahmawati (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
كان الهدف من البحث هو تحديد قدرات الطلاب في مهارات التحدث قبل استخدام نماذج لعب الأدوار وقياس تأثير استخدام نماذج لعب الأدوار على مهارات التحدث لدى الطلاب في المدرسة الحكومية 1 بادنج. طريقة البحث هذه هي بحث كمي من النوع شبه التجريبي حيث تستخدم أدوات جمع البيانات الاختبارات وتحليل البيانات يستخدم اختبارات T. تتكون مصادر البيانات من مديري المدارس والطلاب. وتكونت مواضيع الاختبار من الطلاب. أظهرت نتائج البحث أن مهارات التحدث لدى الطلاب قبل استخدام نموذج لعب الأدوار في المدرسة الحكومية 1 بادنج. يمكن رؤيتها من الاختبار القبلي في الفصل الضابط الذي يعني 59.41 بتقدير ضعيف، وفي الفصل التجريبي المعنى هو 56.28 بتقدير ضعيف. يظهر تأثير استخدام تمثيل الأدوار على مهارات التحدث في في المدرسة الحكومية 1 بادنج إيجابيًا ومعنويًا حيث بلغ متوسط ​​درجة الاختبار البعدي في الفصل التجريبي 90,8 بدرجة جيدة ومتوسط ​​درجة الاختبار البعدي في الفصل الضابط 86,5 بقيمة جيدة. يمكن رؤية هذا البيان من نتائج اختبار الفرضيات باستخدام اختبار t ب independen sample t-test بقيمة sig 2-tailed0،000الأصغر من 0،05، يتم فالفرضية Ha مقبولة والفرضية Ho مردودة. لذلك استنتجت الباحثة أن استخدام نموذج لعب الأدوار يؤثر على مهارة الكلام لطلبة الفصل العاشر في المدرسة العالية الحكومية 1 بادانج. Abstract The aim of the research was to determine students' abilities in speaking skills before using role-playing models and to measure the effect of using role-playing models on students' speaking skills at SMA Negeri 1 Padang. This research method is quantitative research with a quasi-experimental design, where data collection tools use tests and data analysis uses T-tests. Data sources consist of school principals and students. The test subjects consisted of students. The research results show that the students' speaking skills before using the role-playing model at SMA Negeri 1 Padang can be seen from the pre-test in the control class, which mean 59.41 with a weak estimate, and in the experimental class, the mean is 56.28 with a weak estimate. The influence of the use of role-playing on speaking skills at SMA Negeri 1 Padang shows a positive and significant effect, with the average post-test score in the experimental class averaging 90.8, indicating a good score, and the post-test score in the control class averaging 86.5, also with a good value. This statement can be observed from the results of hypothesis testing using the Independent Sample t-test, with a two-tailed significance value of 0.000, which is less than 0.05. The Ha hypothesis is accepted, and the Ho hypothesis is rejected.